2016
DOI: 10.3989/collectbot.2016.v35.001
|View full text |Cite
|
Sign up to set email alerts
|

Nuevos xenófitos de La Palma (Islas Canarias, España), con énfasis en las especies naturalizadas y (potencialmente) invasoras

Abstract: Varios años de trabajos de campo en La Palma (Islas Canarias occidentales) han posibilitado el descubrimiento de nuevas plantas vasculares no nativas. Amaranthus blitoides, A. deflexus, Aptenia cordifolia, Argemone ochroleuca, Begonia schmidtiana, Capsella rubella, Cardamine hamiltonii, Centratherum punctatum, Cerastium fontanum subsp. vulgare, Chasmanthe floribunda (ampliamente confundida con C. aethiopica y Crocosmia xcrocosmiiflora en Macaronesia), Chenopodium probstii, Commelina latifolia var. latifolia, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 23 publications
0
18
0
4
Order By: Relevance
“…In the Canary Islands its presence was noted so far in La Palma (Otto & Verloove 2016) and Tenerife (Verloove, unpublished records). It is here reported for the first time from Gran Canaria where it doubtlessly is relatively frequent but confused with K. daigremontiana.…”
Section: Galinsoga Quadriradiatamentioning
confidence: 85%
See 2 more Smart Citations
“…In the Canary Islands its presence was noted so far in La Palma (Otto & Verloove 2016) and Tenerife (Verloove, unpublished records). It is here reported for the first time from Gran Canaria where it doubtlessly is relatively frequent but confused with K. daigremontiana.…”
Section: Galinsoga Quadriradiatamentioning
confidence: 85%
“…It has long been confused with the similar-looking C. aethiopica (L.) N.E. Brown, not only in the Canary Islands (see Otto & Verloove 2016 for details about their separation) but also elsewhere in Europe, for instance in Italy (Grandis 2016). It was shown that most Canarian populations are in fact referable to C. floribunda, not to C. aethiopica.…”
Section: Part One: Taxa Observed Either In the Wild Or As Weeds In Gamentioning
confidence: 99%
See 1 more Smart Citation
“…Fora de la seua zona d'origen es cultiva com a ornamental en països de clima càlid. Com a escapada de cultiu, a Espanya ha sigut localitzada a l'illa de La Palma (Otto & Verloove, 2016) i a nivell peninsular sols es coneix una cita anterior per a Catalunya, publicada recentment per Gómez-Bellver et al (2019b). Dins del BDBCV s'ha detectat una cita de l'any 1993 referida a Ondara (Alacant), la qual es tracta d'una dada procedent d'un exemplar conreat en jardineria i no naturalitzat (J. X. Soler, com.…”
Section: Panicum Maximumunclassified
“…Even the first, seemingly anecdotic, reproduction of an ornamental is worth reporting, since it may constitute the first (but essential) step in a future naturalization process (Böcker et al, 1995). This paper is a sequel to Otto & Verloove (2016). We present new records for species that are either new to the Canary Islands (and even Macaronesia as a whole) or new to the island of La Palma.…”
Section: Introductionmentioning
confidence: 99%